Government Scale as a Stabilizer: Effects on Output Volatility and Losses - António Afonso; José Alves; Frederico Silva Leal (CESifo GmbH, 2025)
We examine the impact of government size on economic fluctuations and the role of fiscal policy in promoting macroeconomic stability in the period 1980-2024. The results indicate that indirect taxes, capital taxes, and social security contributions (as a percentage of GDP) are associated with lower output volatility, whereas direct taxes tend to amplify it, particularly over longer horizons. On the expenditure side, current spending – especially public wages and interest payments – also exerts a stabilising influence. We further provide new estimates of output losses from the two most severe recent recessions in the EU27 – the Great Recession and the COVID-19 pandemic – and find evidence that the severity of these losses may be linked to the scale of the government, both before and after the crises.
Keywords: E32; E62; H20; 330; government size; fiscal policy; macroeconomic stability; output losses